Comparison of The Provisions On Freedom of Expression On Social Media From A Human Rights Perspective And Law Number 19 of 2016 Concerning Information And Electronic Transactions In Indonesia - Listiyani, Nurul; Christiyana, Yholanda (CV. Inara, 2025)
Freedom of expression is a human right guaranteed by the constitution and various national and international legal instruments. In the era of technological advancement and the rapid use of social media, digital space has become the primary means for people to express opinions and communicate. However, in practice in Indonesia, freedom of expression on social media often experiences conflicts between human rights protections and positive law, particularly Law Number 19 of 2016 concerning Electronic Information and Transactions. Method: Using a normative juridical method with a comparative legal approach and qualitative analysis of primary, secondary, and tertiary legal materials. Materials were collected through a literature review, as well as a literature search related to the regulation of freedom presented both from a human rights perspective and the provisions of the Electronic Information and Transactions Law. Conclusion: While Human Rights provide broad protection for freedom of expression, the Electronic Information and Transactions Law sets limits on the dissemination of information, which has the potential to trigger legal conflicts when restricting expression in the digital space. Harmonization is needed between the protections that state freedom and the regulations of the Electronic Information and Transactions Law to ensure that human rights and public security are maintained on social media.